Sustainability through alloy design: Challenges and opportunities. (April 2021) - Cann, Jaclyn L.; De Luca, Anthony; Dunand, David C.; Dye, David; Miracle, Daniel B.; Oh, Hyun Seok; Olivetti, Elsa A.; Pollock, Tresa M.; Poole, Warren J.; Yang, Rui; Tasan, C. Cem
Abstract: Exciting metallurgical breakthroughs of the last decades alongside the development and wide-ranging availability of new and more capable experimental and theoretical tools for metals research demonstrate that we are witnessing the dawn of a new age in metals design. Historically, the discovery of new metallic materials has enabled the vast majority of the key engineering advances in human history. Current engineering challenges create an urgent need for new metallic materials to further our technological advances in multiple industries that are key to our existence. Yet, present data on metals processing clearly demonstrate the significant environmental impact of the metallurgical industry on our planet's future. There are numerous reports in which this impact and corresponding processing solutions are discussed. On the other hand, design of new metallic materials with improved property combinations can help address key environmental challenges in various ways. To this end, the goal of this review is to discuss the most urgent sustainability challenges that can be addressed with alloy design, to help orchestrate the increasing interest in metallurgical research to focus on these most critical challenges.